Another chance? Concerns about inequality, support for the European Union and further European integration. Issue 7 (20th July 2017) - Simpson, Kathryn; Loveless, Matthew
ABSTRACT: Following the 2007–2008 financial crisis, it was expected that the economic downturn and the widening of economic disparities would produce lower support for the European Union (EU) and its continued integration. Using the 2009 European Election Study (EES) data in 27 EU member states, we find that citizens who see greater economic instability and insecurity, regardless of their current economic status, lower their support for the EU as it is but increase their support for continuing integration. Substantively, this suggests that EU citizens may offer the EU another chance to tackle this timely issue and counterbalance market-generated inequality.